Immuno-profiling of Brucella proteins for developing improved vaccines and DIVA capable serodiagnostic assays for brucellosis - Nandini, Prachita; Jakka, Padmaja; Murugan, Subathra; Mazumdar, Varadendra; Kumar, Deepak; Prakash, Richa; Barbuddhe, Sukhadeo B.; Radhakrishnan, Girish (Frontiers in Microbiology, 2023)
Brucellosis remains a worldwide zoonotic disease with a serious impact on public health and livestock productivity. Controlling brucellosis in livestock is crucial for limiting human infections in the absence of effective human vaccines. Brucellosis control measures are majorly dependent on rigorous monitoring of disease outbreaks and mass vaccination of livestock. Live attenuated vaccines are available for livestock vaccination that play a vital role in brucellosis control programmes in many countries. Even though the existing animal vaccines confer protection against brucellosis, they carry some drawbacks, including their infectivity to humans and interference with sero-monitoring. The available serodiagnostic assays for brucellosis depend on detecting anti-LPS antibodies in the serum. Since diagnosis plays a vital role in controlling brucellosis, developing improved serodiagnostic assays with enhanced specificity, sensitivity and DIVA capability is required. Therefore, it is essential to identify novel antigens for developing improved vaccines and serodiagnostic assays for brucellosis. In the present study, we performed a high throughput immunoprofiling of B. melitensis protein microarray using brucellosis-positive human and animal serum samples.The screening identified several serodominant proteins of Brucella that exhibited common or differential reactivity with sera from animals and humans. Subsequently, we cloned, expressed, and purified ten serodominant proteins, followed by analyzing their potential to develop next-generation vaccines and improved serodiagnostic assays for brucellosis.Further, we demonstrated the protective efficacy of one of the serodominant proteins against the B. melitensis challenge in mice. We found that the seroreactive protein, Dps (BMEI1980), strongly reacted with brucellosis-positive serum samples, but it did not react with sera from B. abortus S19-vaccinated cattle, indicating DIVA capability. A prototype lateral flow assay and indirect ELISA based on Dps protein exhibited high sensitivity, specificity, and DIVA capability. Thus, the present study identified promising candidates for developing improved vaccines and affordable, DIVA-capable serodiagnostic assays for animal and human brucellosis.